2022
DOI: 10.1038/s41598-022-11899-x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of dielectric constant and scan rate on hysteresis effect in perovskite solar cell with simulation and experimental analyses

Abstract: In this work, perovskite solar cells (PSCs) with different transport layers were fabricated to understand the hysteresis phenomenon under a series of scan rates. The experimental results show that the hysteresis phenomenon would be affected by the dielectric constant of transport layers and scan rate significantly. To explain this, a modified Poisson and drift-diffusion solver coupled with a fully time-dependent ion migration model is developed to analyze how the ion migration affects the performance and hyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…This dynamic and thermally activated effect originates from a delayed current response of the device with respect to a change in the external voltage. , Several mechanisms have been proposed as the reasons for hysteresis in perovskites, such as charge carrier trapping and detrapping, , ion migration, , ferroelectric polarization, , and capacitive effects. , It is widely acknowledged that the accumulation of defects at the perovskite/transport layer interface causes hysteresis by influencing the electric field distribution within the device. Several theoretical and experimental studies deduced the relevant time scales related to the migration of defect species in perovskites via quantifying hysteresis as a function of temperature and sweep rate of a J – V measurement. , However, the origin of the ionic defects is still under debate.…”
Section: Types Of Ion Conductionmentioning
confidence: 99%
“…This dynamic and thermally activated effect originates from a delayed current response of the device with respect to a change in the external voltage. , Several mechanisms have been proposed as the reasons for hysteresis in perovskites, such as charge carrier trapping and detrapping, , ion migration, , ferroelectric polarization, , and capacitive effects. , It is widely acknowledged that the accumulation of defects at the perovskite/transport layer interface causes hysteresis by influencing the electric field distribution within the device. Several theoretical and experimental studies deduced the relevant time scales related to the migration of defect species in perovskites via quantifying hysteresis as a function of temperature and sweep rate of a J – V measurement. , However, the origin of the ionic defects is still under debate.…”
Section: Types Of Ion Conductionmentioning
confidence: 99%
“…Moreover, the dielectric constant value ( ε r ) reflects the degree of polarization in the material, indicating that a higher ε r value corresponds to a lower electric field and vice versa . 27 Two spectral regions primarily concern TPV applications. The first is the static dielectric constant, which defines polarization under a constant electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Van Reenen et al and Richardson et al added ion migration into the drift diffusion model to explain the hysteresis phenomenon [20,31]. At present, many researches have also demonstrated that ion migration is the key factor leading to the hysteresis effect, and the joint action of ion migration and carrier recombination causes the hysteresis phenomenon [20,[31][32][33][34]. Furhermore, some factors affecting the hysteresis characteristics of J-V curve have been reported: the material and interface quality of perovskite layer [35][36][37], the use of different transport layer materials [38][39][40][41][42], scanning rate and bias voltage of J-V test [34,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…At present, many researches have also demonstrated that ion migration is the key factor leading to the hysteresis effect, and the joint action of ion migration and carrier recombination causes the hysteresis phenomenon [20,[31][32][33][34]. Furhermore, some factors affecting the hysteresis characteristics of J-V curve have been reported: the material and interface quality of perovskite layer [35][36][37], the use of different transport layer materials [38][39][40][41][42], scanning rate and bias voltage of J-V test [34,43,44]. The passivation of perovskite/transport layer interfaces has been proved to suppress the hysteresis of PSCs experimentally [36,45,46].…”
Section: Introductionmentioning
confidence: 99%